INTENSITAS PERPINDAHAN KEANGGOTAAN PARTAI POLITIK: Sebuah Tinjauan Sikap dan Norma Subyektif Anggota Partai - LUSIA ASTRIKA, LUSIA ASTRIKA (Program Magister Ilmu Politik, Universitas Diponegoro, 2011)
AbstrakBy the Election Day, many political party members move to other parties. This action caninfluence the political stability and deteriorate the political party image from the society’s point of view.This action may not happen if the political party can function and manage their party well. Thismovement starts from the intention to move to other party. This study is aimed to evaluate empiricallythe correlation between attitude and subjective norm on moving to other party with the politicalmembers’ intention to move to other parties. The hypothesis of this research is there is a correlationbetween the attitude and subjective norm of political party members on the movement to other party,and the intention of political party members. The more positive their attitude and the higher thesubjective norm of political party members on moving to other party is , the higher their intention tomove to other party is or vice versa. The data got show that there is a significant positive correlationbetween attitude and subjective norm of the political party members, and the intention of the politicalparty members to move to other party (R = 0,566 with F Regression 20,961 with p < 0, 01).Keyword: Intension, attitude, subjective norm, political party membersA. PENDAHULUAN